DEVELOPMENT OF SOLAR ONION LEAF CUTTER - Avinash D. Sapkal1,Aryan A. Parandkar2,Aditya A. Jadhav2,Sushant R. Mane2 ,Yuvraj B. Zend2 (International Journal of Innovations in Engineering Research and Technology, 2022)
Onion is densely produced crop in India. The harvesting of onion crop is laborious work and requires huge amount of manpower and time. As a part of harvesting of onion, root and shoot has to be trimmed manually, this is a labour oriented process. One of the main reasons of low productivity is low level of mechanization and less technology utilization n. Machine for cutting root and shoot is not available in India and imported machines are expensive and an Indian farmer cannot afford such high price. Farmers incur financial loss because of non-availability of manpower. The purpose of the work is to “design and develop a prototype of onion root and shoot cutting machine” that can cut the root and shoot of onion once fed into the machine. This mechanization will also reduce unit cost of production through higher productivity. The major objective of this work is to reduce total expenses and dependency on labors and to increase the net revenue at an affordable price